USING TECHNOLOGIES AND INTERACTIVE METHODS IN TEACHING SPEAKING FOR INTERMEDIATE LEVEL OF STUDENTS (Web of Teachers: Inderscience Research, 2024)
This extensive research paper conducts an in-depth exploration into the multifaceted realm of integrating technology and interactive teaching methods to enhance speaking skills among intermediate-level students. Through a comprehensive analysis of various digital tools and interactive techniques, this study aims to elucidate the nuanced dynamics at play in fostering oral communication proficiency and student engagement within language learning contexts. By meticulously examining the interplay between technology, pedagogy, and learner outcomes, this research endeavors to provide a rich tapestry of insights into effective strategies for optimizing speaking instruction. Furthermore, this paper seeks to make a significant contribution to the ongoing discourse surrounding innovative approaches to language education, particularly in the domain of technology-enhanced learning, by offering nuanced perspectives and empirically grounded findings.